(3GdeaGgje GdCNdGbjI Hjf GdGFJeGfjI hGdYdeGfjI (B/s - (3YHO GdQMef , Wgs 1944- ((3GdchjJ (B:s (3dHfGf (B:s (3eQcR fghV ddOQGSGJ hGdHMhK ,s, 2021)
(S0(3GdeaGgje GdGFJeGfjI(S1 (3HebOeI Yf cjajI GdJhSd HGdeYGfj GdEjeGfjI ddhUhd ddeTJQc GdadSaj GdCNdGbj, hKfi HGdaUhd eHJOFG EjGgG HMGLI GdeLJeY GdYGdej ddfXQjI GdGFJeGfjI, Ke GdehGKjb GdKdGKI HhGbY aUd dcd ejKGb hKdK HedMbjf, GdChd (B: (3Yf cjajI LYd GdeYGfj GdEjeGfjI COhGJ JMdjdjI, hGdKGfj (B: (3Yf efXhQ GdGFJeGf hLeY GdbQBf, aNGJeI hegO ddLRA GdKGfj (S0(3GdeaGgje GdYdeGfjI(S1(3, Ke YGdL aj GdaUhd GdeaGgje GdCNdGbjI GdeYGUQI HGdadSaI GdGFJeGfjI OGaYG YdefI(B-(3aUdg Yf GdEjeGf(B-(3Gdeaghe HCjefJg(B-(3hUdg HGdEjeGf(B-(3hjdMX GdbGQF Cf CcKQ GdeaGgje GdeYGdLI gj ef GdeLGd GddZhj GdEfLdjRj hGdSjGb GdehSY ddYdeGfjI, hgj (B: (3GdeYjGQjI GdCNdGbjI, hGdCeQ GdEdgj, hGdbjeI, hGdKbI, hGdeSDhdjI GdMVGQjI, hGdYOGdI GdYGdejI ; Ke NJe HedMb Yf GdYGdejI GdGFJeGfjI hGdSDGd GdSjGSj hHfjI GdcJGH GdYGeI Hjf GdJfXjQ hGdJWHjb gj (B: (3ZdH Ydi GdLRA GdChd GdJfXjQ dHfGA GdeaGgje GdGFJeGfjI, hGdLRA GdKGfj eMd JWHjb GdHfGA GdfXQj dfbO GdeaGgje GdCNdGbjI aj GdeLGd GdacQj hGdadSaj GdeYGUQ(B.s
(3GdeMJhjG J (B: (3L(B1. (3GdeaGgje GdGFJeGfjI (B- (3L(B2. (3GdeaGgje GdYdeGfjI(B.s
(3jTJed Ydi edGMb(B.s
(3jTJed Ydi HHdjhLQGajI(B.s
Keywords: (3KbGaI ESdGejIs -- (3GdCNdGbs -- (3adSaIs -- (3GdESdGe hGdYdeGfjIs -- (3GdESdGe hGdCNdGbs